Model‐based Engineering of Emergence in a Collaborative SoS: Exploiting SysML & Formalism. (28th October 2015) - Ingram, Claire; Payne, Richard; Fitzgerald, John; Couto, Luis Diogo
Abstract: A collaborative SoS is a system composed of constituent systems (CSs), which are independent and voluntarily cooperate without an agreed SoS director. Engineering emergent behaviour is just one of the key engineering challenges for which support is needed. In this paper we illustrate for the first time an integrated collection of model‐based techniques for verifying behaviours and properties, with the aim of assisting the engineering of collaborative systems of systems (SoSs). We provide an illustration of an approach that flows from requirements and architectural modelling to the use of formal techniques, integrating methods drawn from software and systems engineering fields to tackle engineering challenges in SoS. The approach incorporates architectural modelling (implemented in SysML) before transitioning to a formal modelling notation which has been developed specifically for SoSs. This formal modelling approach supports a wide range of analysis and verification techniques, such as: design space exploration; requirements verification; and consistency checks. We also discuss how our approach can be incorporated into a standard systems engineering approach.